Assessing the challenges experienced by caregivers in implementing inclusive education at early childhood education (E.C.E) level at Lotshe Primary School in Bulawayo African Township (B.A.T) cluster in Reigate district, Bulawayo Metroprovince - Ndlovu, Sijabulisiwe (2019)
The aim of this study was to assess the challenges faced by caregivers in implementing inclusive education at ECE level at Lotshe Primary School in B.A.T cluster, Reigate District. A qualitative approach and descriptive survey design were used in this study. The population consisted of ECE teachers and parents. The sample comprised ten teachers and five parents. Purposive sampling technique was used to select the participants. Questionnaires were used for teachers while interviews were used for parents. The study revealed teachers faced challenges in implementing inclusive education. These are lack of expertise/ knowledge, shortage of resources, inadequate infrastructure, teacher pupil ratio. The study recommended that teachers should engage in in-service training and attend to seminars and workshops. The study further recommended the infrastructure should be renovated to accommodate all learners.